Evaluation Analysis of The Implementation of The Merdeka Belajar - Kampus Merdeka (MBKM) Program: A Literature Review - Nafisah, Nisa’atun; Fikri, Muhammad Afiq; Zuhriyah, Indah Aminatuz (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of the Merdeka Belajar - Kampus Merdeka (MBKM) program is to provide flexibility for students in choosing subjects, extracurricular activities, and skill development opportunities beyond those offered by the campus. The main objective of this program is to equip Indonesian students with the knowledge and abilities they need to succeed in the competitive world of work. The purpose of this literature review is to examine the past and current use of the MBKM Program in academic settings. A literature review of relevant papers, scientific journals, and other publications on the MBKM Program was conducted to learn more about the implementation, challenges, and benefits of the program. Several important conclusions can be drawn from the results of this literature review. First, the MBKM Program has not been fully implemented in higher education, and there are several obstacles that must be overcome. Second, problem solving will be more efficient if all interested parties work together. Evaluating the implementation of the MBKM Program is essential to make it more successful. By conducting a literature review, the university can learn about new problems, develop plans to address those problems, and improve the learning opportunities available to its students. By providing a greater understanding of the issues and challenges faced in implementing the MBKM Program in higher education, this literature review helps in improving the implementation of the program, overcoming barriers, and maximizing the benefits received by students.